2021
DOI: 10.1021/acs.jpcc.1c07409
|View full text |Cite
|
Sign up to set email alerts
|

Localized Surface Plasmon Resonance as a Tool to Study Protein Corona Formation on Nanoparticles

Abstract: It is now well-accepted that nanoparticles (NPs) introduced into a biological environment will interact with the available proteins that deposit on their surface in a process known as protein corona (PC) formation which control NP interactions with cells and biological barriers. Several investigations have been conducted to understand the mechanisms and kinetics of PC formation. Among the model nanoprobes are gold (Au) NPs that possess unique optical and electromagnetic properties due to their surface plasmon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 106 publications
2
15
0
Order By: Relevance
“…Notably, the increase in the f ( η 2 ) values evidences the NAV adsorption on lf-SWCNTs-b because it is reported that the estimated f ( η 2 ) values were 0.338 and 0.510 for D 2 O ( η D2O = 1.328) and the proteins ( η protein = ∼1.6 54,55 ), respectively. Focusing on the absolute values for Δ E 11 * and Δ E 11 (|Δ E 11 *| and |Δ E 11 |, respectively), the |Δ E 11 *| value was higher than the |Δ E 11 | value.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Notably, the increase in the f ( η 2 ) values evidences the NAV adsorption on lf-SWCNTs-b because it is reported that the estimated f ( η 2 ) values were 0.338 and 0.510 for D 2 O ( η D2O = 1.328) and the proteins ( η protein = ∼1.6 54,55 ), respectively. Focusing on the absolute values for Δ E 11 * and Δ E 11 (|Δ E 11 *| and |Δ E 11 |, respectively), the |Δ E 11 *| value was higher than the |Δ E 11 | value.…”
Section: Resultsmentioning
confidence: 91%
“…Negative-value signals are observed for ΔE 11 * and ΔE 11 because of the red-shifts of the PL peaks upon the introduction of the NAV. These values decreased further as the NAV concentration increased and eventually reached saturation at 250 nM.Notably, the increase in the f (η 2 ) values evidences the NAV adsorption on lf-SWCNTs-b because it is reported that the estimated f (η 2 ) values were 0.338 and 0.510 for D 2 O (η D2O = 1.328) and the proteins (η protein = ∼1.654,55 ), respectively.Focusing on the absolute values for ΔE 11 * and ΔE 11 (|ΔE 11 *| and |ΔE 11 |, respectively), the |ΔE 11 *| value was higher than the |ΔE 11 | value. This indicates the selective adsorption of NAV on the biotin-doped sites of lf-SWCNTs-b.…”
mentioning
confidence: 88%
“…28 Therefore, the investigation of physical chemistry perspectives through spectroscopic techniques and theoretical models to characterize the thermoplasmonic characteristics is indispensable to augment the conception from the colloidal dispersion inside the living cells. 29 In this article, we have demonstrated a thermoplasmonic footstep toward the in vitro photothermal reshaping of onedimensional plasmonic polymers upon laser-induced melting in confined media like a cellular environment. Five different sets of plasmonic polymers obtained through interdigitation of size-selective constituent monomers have been internalized, and subsequent photothermal reshaping leads to the transformation to quasi-rod-like nanostructures with different aspect ratios.…”
Section: Introductionmentioning
confidence: 98%
“… 28 Therefore, the investigation of physical chemistry perspectives through spectroscopic techniques and theoretical models to characterize the thermoplasmonic characteristics is indispensable to augment the conception from the colloidal dispersion inside the living cells. 29 …”
Section: Introductionmentioning
confidence: 99%
“…The protein corona plays a major role in forming nano-aggregates. In order to characterize the aggregation of the bio-nano particles, understanding the conformation ofa forming protein corona is invaluable to design new bio-nano-materials [1] , [6] , [8] , [9] . A layer of protein corona was divided into two regimes: hard and soft.…”
Section: Introductionmentioning
confidence: 99%